TEACHERS' DIFFICULTIES IN IMPLEMENTING THE INDEPENDENT CURRICULUM IN THE LEARNING PROCESS AT STATE ELEMENTARY SCHOOL GAROT ACEH BESAR - Nurkamaliah, Siti; Fauzi, Fauzi; Mislinawati, Mislinawati (Elementary Education Research, 2024)
This research aims to determine the difficulties teachers have in implementing the independent curriculum in the learning process at SD Negeri Garot Aceh Besar. This research uses a qualitative approach with descriptive research type. The research subjects were teachers of grades I, II, IV and V. Data collection was carried out by observation, and interviews. The data analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. The research results show that teachers' difficulties in implementing the independent curriculum in planning, implementing and assessing learning are difficulties in analyzing CP, formulating TP and compiling ATP and Teaching Modules, determining learning methods and strategies, lack of ability to use technology, limited student books, lack of ability and readiness. using learning methods and media, teaching materials are too broad, determining class I, II, IV and V projects, lack of time allocation for project-based learning, determining the form of assessment and form of assessment in project-based learning. Based on the research results, it can be concluded that teachers' difficulties in implementing the Independent Curriculum for the Learning Process at the Garot Aceh Besar State Elementary School are in implementation planning and learning assessment.